Development of Eagle Eye as the Foul Service Detector at Service Circle in Sepak Takraw Game (Journal of Physical Education and Sports, 2019)
The development of science and technology in sports plays an important role in the improvement of sports achievement in Indonesia. The use of media and application in sepak takraw is also essential in providing opportunities for athletes, referees, coaches, and officials to widen their knowledge related to the application of science and technology which support sepak takraw. This research is aimed to find out the design of eagle eye devices that detect foul service circle in sepak takraw game to facilitate the referee in making sure about errors or failures in service implementation and to provide evidence of violations committed by tekong. Knowing the effectiveness of eagle eye devices that detect foul service circle in the sepak takraw game developed. This research is development research. The procedures of product development include the analysis of the product to be developed, developing an initial product, expert validation and revision, small group trial and revision, large group trial, and final product. Data collection was carried out by using a questionnaire from expert evaluation as well as an observation on the field obtained from athletes, referees, coaches, and sepak takraw officials. The data analysis technique used was the descriptive percentage analysis. Based on the result of the research, the design of the eagle eye device is in the form of a webcam camera arranged with a tripod which connected via Bluetooth control to the eagle eye application on the laptop. Research on the effectiveness of eagle eye device, which was conducted by electronic experts obtained a mean score of 3.73 with â€œvery goodâ€ category. Research from sepak takraw experts obtained a mean score of 3.45 with â€œgoodâ€ category. Small group trials that have been carried out showed a result of â€œvery goodâ€ category with a percentage of 98.3%. The result from large group trials reached the category of â€œvery goodâ€ with a percentage of 98.6%. The conclusion of this research is product development of eagle eye detection of service foul in service circle can be used as a mean to help referee performance when leading sepak takraw match to provide evidence of violations during the match.